Discrete-time Modeling and Numerical Evaluation of BER Performance for A BPSK-based DCSK-Walsh Coding Communication System over Multipath Rayleigh Fading Channels - Doan, Thi Que; Nguyen, Xuan Quyen; Hoang, Thang Manh (Old Journal, 2017)
This paper investigates the use of binary phase shift keying (BPSK) modulation for multiple-access communication systems based on differential chaos shift keying-Walsh Coding (DCSK-WC). This aims at converting the chaotic-modulated signal from low-frequency baseband into high frequency band before being transmitted on the channel. In the transmitter, a chaotic sequence is transformed into the non-return-to-zero (NRZ) form which is then fed into the BPSK modulation. The output of modulation, i.e., NRZ-Chaos/BPSK signal, is used as a spreading code in the DCSK-WC modulation. The process of data recovery in the receiver is performed by means of the correlation calculation and energy detection as in the conventional DCSK method. The mathematical model in discrete-time domain describes the operation of the transmitter and receiver over multipath Rayleigh fading channels. The Bit-error-rate performance of the system is evaluated by numerical simulation. The results show that the proposed BPSK/DCSK-WC system allows adjusting the operating frequency band with the use of BPSK, while still keeping the performance equivalent to that of the conventional one.